MODELOS GLEN DOMAN Y EL MODELO MONTESSORI Y SU IMPACTO EN EL APRENDIZAJE DE NIÑOS CON TDAH DE 2DO AÑO DE EGB DE LA ESCUELA AURORA ESTRADA Y AYALA DE RAMÍREZ PÉREZ DE LA CIUDAD DE BABAHOYO - CHACHA FAJARDO BRITHNEY JULADY (2024)
Research on the Glen Doman and Montessori model in students with ADHD suggests that these educational approaches can provide significant benefits. Both methods focus on more individualized, active, and experiential learning, which can be especially beneficial for students by providing a more structured and stimulating learning environment. Studies have shown improvements in attention, behavior, and academic performance of students who have been exposed to these educational approaches. However, more research is needed to fully understand its impact and applicability in different educational contexts. The Glen Donan model is an educational intervention strategy that focuses on adapting the school environment to meet the needs of students (Attention Deficit Hyperactivity Disorder). Research has shown that this approach can improve students' academic performance, self-esteem, and behavior by providing structure, individualized support, and self-regulation techniques. This model also emphasizes collaboration between teachers, parents, and health professionals to ensure a comprehensive approach in managing the school environment. Research on the Montessori model and its impact on students with ADHD has found mixed results. Some studies suggest that the Montessori approach, which encourages autonomy, independent learning, and the use of manipulative materials, may benefit some students by providing a more structured and flexible learning environment. However, other studies have found that the Montessori approach may not be suitable for all students, as freedom and self-direction can present challenges for those who have difficulty concentrating or maintaining attention. Overall, more research is needed to fully understand how the Montessori model can be effectively adapted to meet the needs of students with ADHD.